Preliminary Investigation on Sodium Alginate Extracted from Sargassum Subrepandum of Red Sea of Eritrea as Tablet Binder - Basha, N. S.; Rekha, R.; Letensie, A.; Mensura, S. (Journal of Scientific Research, 2011)
Natural polysaccharides hold advantages over synthetic polymers for conventional and novel dosage forms, because these are non-toxic, less expensive, and biodegradable. These can also be modified to tailor-made materials and thus can compete with the available synthetic excipients. Therefore, the aim of present work is to extract sodium alginate from the seaweed S. subrepandum to assess its binding property using propranolol as model drug. Sodium alginate was extracted by room-temperature alkaline extraction and high-temperature (80°C) alkaline extraction methods. Binding strength was evaluated by using two different formulations i.e., formulation 1 with sodium alginate as a binder and formulation 2 with hydroxypropylmethylcellulose (HPMC) as reference standard. The two tablet formulations were evaluated and compared for parameters such as friability, hardness and disintegration. The percentage yield was found to be 17.5% w/w by room-temperature alkaline extraction and 21%w/w by high-temperature extraction method. The results obtained for all tested parameters for tablets with sodium alginate were found within acceptable range of USP standards. It was also founded that both sodium alginate and HPMC have similar binding strength at similar concentration. So, it can be concluded that sodium alginate of S. subrepandum can be used as suitable alternative binder in tablet formulations. Keywords: Sargassum subrepandum; Sodium alginate; Hydroxypropyl methylcellulose; Friability; Hardness; Disintegration. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.6770 J. Sci. Res. 3 (3), 619-628 (2011)